Antisipasi Persedian Oli Sepeda Motor Wilayah Karawang dengan Menggunakan Pendekatan Knowledge Discovery in Database (KDD) - Riyadi, Taufan (AI Society & STMIK Indonesia, 2024)
Sales plays a very important role in the motorcycle oil retail business. High sales numbers indicate the health of the business and help ensure the continued operation of the retail store. With good sales, retail stores can earn enough income to cover operational costs, make a profit, and even expand their business. Therefore, it is important for retail store owners to manage the sales process effectively and ensure that the goods offered match customer needs and desires. Product availability is very important so that a sales transaction is not lost. One way to deal with this problem is to carry out research to find out sales patterns, making it easier for entrepreneurs to buy back stock to fill their retail shop's oil needs so that there are no lost sales transactions which will affect their income. The Apriori algorithm is one of the basic algorithms for determining high frequency patterns that often appear. This research uses sales data from retail motorbike oil sales in Indonesia, which has 91 XYZ retail stores spread across Karawang Regency. The result of this research is that the most sold oil products are known, so it can make it easier for entrepreneurs to find out the most sold products and can be used as a reference if they want to increase their inventory and promote strategies for oil products that are still selling poorly